Adolescent Coping Strategies with Parental Divorce: A Narrative Review - Iyus Yosep; Ai Mardhiyah; Rohman Hikmat (Institute of Computer Science (IOCS), 2022)
Parental divorce is one of the long-term stresors in children that can have negative impacts such as difficulty in building relationships, communicating, often feeling anxious, and irritable. So that adaptive coping is needed in dealing with these stresors. There are two coping strategies, namely emotional-focused coping and problem-focused coping, as well as adaptive and maladaptive categories. Therefore, the purpose of this study was to explore the coping strategies of adolescents with divorced parents. Methods: This study used the Narrative Review method. Literature review through Ebsco, Pubmed, Science Direct, Sage Journals, and Google Scholar databases. The keywords used in English are